PENGARUH FAKTOR-FAKTOR PENJUALAN TERHADAP PENJUALAN PRODUK LGS MATAHARI DEPARTEMENT STORE CIPUTRA SERAYA PEKANBARU - Agustarizal (P3M STKIP 'Aisyiyah Riau, 2014)
This study aims to determine the influence of the factors that influence the sale of LGS products at Matahari Department Store Ciputra Seraya. The place of this research was conducted at the Matahari Department Store Ciputra Seraya Pekanbaru with 32 research samples taken randomly. The data collection technique is done by using a questionnaire for internal factors and external factors and documentation to obtain sales data. The data obtained in the field is processed using simple linear regression analysis. Based on the results of research and discussion, it can be concluded that there are influences from internal and external factors on sales at the Ciputra Department store while Pekanbaru. The influence of internal factors and external factors on sales obtained a correlation coefficient of 0.650, so that the influence of internal and external factors on sales obtained is R2 that is 0.500 or 50.04% based on the conclusions suggested about the importance of increasing service quality factors to sales and event promotion factors by means of procurement of facilities, media, and methods of increasing sales.